Ramified derivatives of 5-(perylen-3-ylethynyl)uracil-1-acetic acid and their antiviral properties. Issue 45 (20th August 2019) - Sapozhnikova, Ksenia A.; Slesarchuk, Nikita A.; Orlov, Alexey A.; Khvatov, Evgeny V.; Radchenko, Eugene V.; Chistov, Alexey A.; Ustinov, Alexey V.; Palyulin, Vladimir A.; Kozlovskaya, Liubov I.; Osolodkin, Dmitry I.; Korshun, Vladimir A.; Brylev, Vladimir A.
Abstract : Ramified clusters of antiviral perylenylethynyl scaffold were prepared using CuAAC reaction of 5-(perylen-3-ylethynyl)-3-pivaloyloxymethyl-1-(propargylamidomethyl)uracil with azides. Compounds inhibited TBEV reproduction at nanomolar concentrations. Abstract : The propargylamide of N3-Pom-protected 5-(perylen-3-ylethynyl)uracil acetic acid, a universal precursor, was used in a CuAAC click reaction for the synthesis of several derivatives, including three ramified molecules with high activities against tick-borne encephalitis virus (TBEV). Pentaerythritol-based polyazides were used for the assembly of molecules containing 2⋯4 antiviral 5-(perylen-3-ylethynyl)uracil scaffolds, the first examples of polyvalent perylene antivirals. Cluster compounds showed enhanced absorbance, however, their fluorescence was reduced due to self-quenching. Due to the solubility issues, Pom group removal succeeded only for compounds with one peryleneethynyluracil unit. Four compounds, including one ramified cluster9f, showed remarkable 1⋯3 nM EC50 values against TBEV in cell culture.